Strategic Culture of the United States in the 2022 Indo-Pacific Strategy - Sean Gaudialmo; Jelang Ramadhan (Universitas Negeri Semarang, 2025)
A country's foreign policy can be based on its strategic culture, and the US is no different with its Indo-Pacific Strategy 2022. The US strategic culture includes American exceptionalism and moral crusade, technology and firepower-intensive warfare, and free security combined with projection of power. The author intends to bring a novelty by analyzing the strategic culture in the Indo-Pacific Strategy 2022. Furthermore, the study uses a constructivist approach to emphasize the role of identity, values, and norms in shaping the US Indo-Pacific Strategy. This study finds that the U.S. and China share similar strategic cultures but use different narratives to win their rivalry, with U.S. strategic culture mostly staying consistent while evolving across administrations, and being shaped by American values in law supremacy and order, human rights and equality, liberalism, and American exceptionalism. The findings of this research contribute to the development of American studies by demonstrating that U.S. foreign policy has consistently served as a space where American values and culture are represented, distributed to other countries, and influence the formation of future American cultural expressions, revealing the US’ interpretation of the Indo-Pacific in pursuit of its national interests.